Análisis del discurso que maneja la actual administración del Centro Deportivo Olmedo, período enero-octubre 2022. - Ibarra Ortega, Ambar Anahí (2023)
ABSTRACT: Discourse analysis is a discipline of study that focuses on examining the language used in different contexts to understand how meanings are built, ideas are communicated, and power is exercised through discourse; it is a powerful tool to unravel how senses are built, power is exercised, and social structures are reflected through language. It is used in various fields and is essential to understand how reality is communicated and negotiated in our society. The present research aims to know what discourse has been handled for its target audience at the Olmedo Sports Center by its current administration. This qualitative analysis uses a matrix of analysis and interviews with its respective questionnaires. These data were analyzed in the 2022 season, January-October, through his Facebook page and the most relevant media where he has conducted interviews. Among the results obtained, the discourse handled within the club of the city of Riobamba is evident, where the significant difference that this leadership has with the previous ones when taking a motivational and frontal discourse is noticeable.